Effect of calorie restriction and intermittent fasting on glucose homeostasis, lipid profile, inflammatory, and hormonal markers in patients with polycystic ovary syndrome: a systematic review - Kalsekar, Anam S.; Abdelrahim, Dana N.; Faris, MoezAlIslam E. (Frontiers in Nutrition, 2024)
Background & Objective. Polycystic ovary syndrome (PCOS) is a complex hormonal disorder that leads to ovarian cysts, irregular ovulation, and hormonal swings in women. It is a complex and heterogeneous condition that affects 4% to 20% of women of reproductive age worldwide and relates to reproductive, metabolic, and psychosocial dysfunction. Dietary and lifestyle modifications have been proposed to play a central role in the management of PCOS. This study aimed to provide a comprehensive systemic overview of the existing literature on the effects of intermittent fasting (IF) and calorie restriction (CR) regimens on disease markers of PCOS. Designs & Methods. Several databases, such as CINAHL, Cochrane, EBSCOhost, EMBASE, Google Scholar, ProQuest Medical, PubMed/MEDLINE, ScienceDirect, Scopus, and Web of Science databases were searched for clinical trials and observational studies examined the effects of IF regimens such as time-restricted eating and Ramadan model of IF (RIF) on glucose homeostasis, lipid profile, inflammatory and hormonal markers in patients with PCOS. Results. This systematic review solicited three articles, comprising a collective sample size of 75 females diagnosed with PCOS. The studies were published between 2015 to 2023 and were undertaken in three countries: China, Turkey, and Iran. The research articles examined the effects of intervention with IF and CR on PCOS-related parameters such as anthropometric measures and biochemical tests which included enzymes, glycemic control, lipid profile, hormonal, and oxidative stress, and inflammatory markers. The articles yielded mixed results, with two of them showing significant changes across all tested parameters. One of the three studies did not exhibit any significant changes. Conclusion. Very limited studies examined the relationship between IR and CR with markers of PCOS. Further well-controlled studies need to be undertaken The combined results from the limited studies illustrate the intricate and diverse nature of IF, including the RIF, and its influence on measurements of body composition and biochemical markers related to PCOS.